Genre Based Approach An Alternative in Teaching Comparison and Contrast Essay - Basori Basori (JETLe (Journal of English Language Teaching and Learning), 2020)
Writing as one of the productive skills is offered as a required course in many English language program at many universities. However, research showed that teaching writing skill faced some challenges. Therefore, this article offered an approach that shed the light. The article discussed a description of what a comparison and contrast essay in general, the definition of Genre Based Approach in teaching writing and the application of GBA in teaching comparison and contrast essay. The article serve as a reference for teachers in teaching comparison and contrast essay for academic writing and other purposes.